Theoretical Study of Vibrational Frequencies and Chemical Shifts of Choline Halides (F, Cl, Br) - Mustafa Karakaya; Fatih Ucun; Ahmet Tokatlı; Semiha Bahçeli (Süleyman Demirel Üniversitesi Fen-Edebiyat Fakültesi Fen Dergisi, 2010)
The vibrational frequencies and 1H and 13C chemical shifts of choline halides have been calculated using density functional theory (B3LYP) method with 6-311++G(d, p) and 6-31 G(d, p) basis set level in Gaussian 03 and Parallel Quantum Solutions (PQS) ab initio packages programs, respectively. The calculated optimized geometric parameters, vibrational frequencies and chemical shifts were seen to be a very good agreement with the experimental data. The electronegativity influence of the halogen substitutions on the vibrational frequencies and chemical shifts have also been investigated. It was observed that the chemical shifts for H nucleus, especially the most near nucleus to the halogen atom decrease while it increases for C nucleus. The roughly linear variation of the chemical shift with the electronegativity of the halogen, whatever the shielding for C nucleus or deshielding for H nucleus is, has been commented that the local electron density near the halogen atom is affected.